3D STATIC RESERVOIR MODELING AND HYRDROCARBON RESERVE ESTIMATION OF RESERVOIR-1 INTERVAL, TALANGAKAR FORMATION, LOTSO FIELD, SUB-BASIN OF SOUTH PALEMBANG, SOUTH SUMATRA BASIN - Reyhan Irfan, Salma
Lotso Field has an upside resource potential on Talangakar Formation as indicated by the presence of gas based on the result of tested data on exploration wells. Lotso field has been producing oil since 1939 and constantly being developed. Administrively, Lotso Field located in Prabumulih City, South Sumatra Province. This field is physiographically part of South Palembang Sub-basin which lies in Tertiary-aged of South Sumatra back-arc basin. Geological studies and reservoir modelling are focused on Talangakar Formation with one reservoir interval comprise of sandstones and shale respectively. This study aims to comprehend the geological condition, determinating static reservoir model, and estimating hydrocarbon reserve from one reservoir in Lotso Field. Data used in this study consist of wireline log, side wall core description, biostratigraphy report and three dimensional seismic data. Several methods used in this study comprise of well correlation using sequence stratigraphy concepts, biostratigraphy analysis, petrophysical analysis, analysis of facies and depositional environment, isopach determination, creating depth structure map using seismic data; three dimensional structural model, facies and petrophysical properties models; determination of fluids contact and hydrocarbon reserve estimation. Based on those methods mentioned above, the Reservoir-1 interval was deposited on lower delta plain which consists of distributary channel, interdistributary bay, crevasse splay, and floodplain. The main geological structure in Lotso Field consists of northwest-southeast orientation of anticline associated with inversion fault and normal faults with northeast-southwest orientation. The cutoff of petrophysical properties obtained from the analysis are Vsh = 0.55; PHIE = 0.10; Sw = 0.80. The estimation of hydrocarbon reserve (IGIP) from four reservoir give the value around 11.09 bscf.